Optimalisasi Kuis Berbasis Moodle untuk Evaluasi Pembelajaran Akuntansi di Era Digital - Abdullah Affandi; Balqis Fitri Alifya; Anjelina Anjelina (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
Technological developments also affect the teaching and learning process. One of them is the learning evaluation process that can be done online through the Moodle platform. This research will focus on making effective quizzes on the Moodle platform, as well as looking at the effectiveness and response of teachers and lecturers in accounting courses. The type of quiz chosen is embedded answers, where the quiz can be modified at will using a coding formula from Moodle. The pretest-post test method was carried out to see the effectiveness of the quiz on students. Collecting data related to student responses will use questionnaires, while lecturer responses are carried out by means of interviews. The subjects of this study were D3 Accounting students at the Batam State Polytechnic. The results of this study, students get a higher average score when carrying out Moodle-based quizzes than quizzes manually. As many as 70% of students also agree that Moodle-based quizzes are more effective than manual quizzes. In addition, Moodle-based quizzes provide many benefits for both teachers and students.